Inhibition of c‐Met promoted apoptosis, autophagy and loss of the mitochondrial transmembrane potential in oridonin‐induced A549 lung cancer cells. (15th September 2013) - Liu, Ying; Liu, Jian‐Hong; Chai, Kuan; Tashiro, Shin‐Ichi; Onodera, Satoshi; Ikejima, Takashi
Abstract Objective Herein, inhibition of hepatocyte growth factor receptor, c‐Met, significantly increased cytochrome c release and Bax/Bcl‐2 ratio, indicating that c‐Met played an anti‐apoptotic role. The following experiments are to elucidate this anti‐apoptotic mechanism, then the effect of c‐Met on autophagy has also been discussed. Methods Investigated was the influence of c‐Met on apoptosis, autophagy and loss of mitochondrial transmembrane potential (Δψm), and the relevant proteins were examined. Key findings First, we found that activation of extracellular signal‐regulated kinase (ERK), p53 was promoted by c‐Met interference. Subsequent studies indicated that ERK was the upstream effector of p53, and this ERK‐p53 pathway mediated release of cytochrome c and up‐regulation of Bax/Bcl‐2 ratio. Secondly, the inhibition of c‐Met augmented oridonin‐induced loss of mitochondrial transmembrane potential (Δψm), resulting apoptosis. Finally, the inhibition of c‐Met increased oridonin‐induced A549 cell autophagy accompanied by Beclin‐1 activation and conversion from microtubule‐associated protein light chain 3 (LC3)‐I to LC3‐II. Activation of ERK‐p53 was also detected in autophagy process and could be augmented by inhibition of c‐Met. Moreover, suppression of autophagy by 3‐methyladenine (3‐MA) or small interfering RNA against Beclin‐1 or Atg5 decreased oridonin‐induced apoptosis. Inhibition of apoptosis by pan‐caspase inhibitor (z‐VAD‐fmk) decreased oridonin‐induced autophagy as well and Loss of Δψm also occurred during autophagic process. Conclusion Thus, inhibiting c‐Met enhanced oridonin‐induced apoptosis, autophagy and loss of Δψm in A549 cells.